Kebijakan Keamanan Energi - Keliat, Makmur (Global: Jurnal Politik Internasional, 2006)
The discussion on the importance of energy security policy for Indonesia merits special attention for a number of reasons. First, there has been an opinion that the recent decision by government to increase the price of fuel energy can be attributed to its short sighted view on energy security policy. Secondly, the idea of energy security has evolved from its original concept to the effect that the main concern is currently not merely over the question of how to secure sufficient supply of energy at affordable price but also over its future sustainability. Thirdly, there have been contending paradigms in designing policy to achieve energy security namely between those who consider energy as market commodity and those who regard it as a strategic commodity. The paper primarily attempts to answer the following questions: what is energy security policy and why should energy security policy be comprehensive? For the purpose of analysis, the paper is divided into three parts. The first part attempts to define what we mean by energy with special reference to heat energy including its various dimensions and categories. The second part aims at tracing the rationale behind the emergence of energy security including its evolvement as a concept. The third part intends to show policy options available for policy makers in designing energy security policy by locating and seeing them through the lenses of contending paradigms. Since the recent hike of fuel energy has strong tendency to take side with and seems to have been inspired by market paradigm, an attempt is also made in the last part of the paper to analyze deficiencies of Indonesian current energy security policy.